2014
DOI: 10.4236/ojn.2014.44031
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin Induced Neurotoxicity among Patients with Colorectal Cancer: Documentation in Medical Records—A Pilot Study

Abstract: Patients with colorectal cancer (CRC) can have chemotherapy with oxaliplatin postoperatively. Oxaliplatin can cause acute and chronic neurotoxicity. It is important to be aware of neurotoxic side effects so they can be documented and action taken at an early stage. The study aimed to identify and explore neurotoxic side effects documented in the medical records of patients with colorectal cancer treated with oxaliplatin-based adjuvant chemotherapy. Data in this study were medical records; presenting documentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Free descriptions of the physician's estimation of the patient's neurotoxic symptoms in the medical records were analysed. All symptoms in the predetermined protocol influenced by the Swedish version of the OANQ were found in the medical records except "heat sensitivity" (24). This finding also strengthens the content validity of the questionnaire (27).…”
Section: Validity Of the Oanqsupporting
confidence: 62%
See 2 more Smart Citations
“…Free descriptions of the physician's estimation of the patient's neurotoxic symptoms in the medical records were analysed. All symptoms in the predetermined protocol influenced by the Swedish version of the OANQ were found in the medical records except "heat sensitivity" (24). This finding also strengthens the content validity of the questionnaire (27).…”
Section: Validity Of the Oanqsupporting
confidence: 62%
“…The scale ranges from 1 to 5 with a higher score indicating greater severity of the symptom and affect of daily activities. The original OANQ is in English (21) and was translated to Swedish and adjusted to Swedish settings (24). The translation of the OANQ to Swedish and back translation to English was conducted in three steps (25)(26).…”
Section: Identifying Risk Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, even though most studies applied dose reduction criteria in order to limit the degree of subsequent toxicity, the number of patients who received reduced dose, treatment delay and treatment cessation due to acute neuropathy was reported in one study only [ 25 ]. The lack of a systematic, detailed approach to presentation of the number of patients who received dose reduction (and when) and dropout rates within the first cycle, means that the impact of such parameters on subsequent treatment cannot be informed by comprehensive data sets, making dose modification difficult in order to limit the development of acute and chronic neuropathies [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, no study reported the number of patients whose symptoms resolved and those who had persistent neuropathy in the second cycle among who developed acute neuropathy in the first 14 days of chemotherapy. This will hamper preventive actions and treatment optimization at the early stage of treatment [ 43 ]. Moreover, studies differed in starting dose (duration of infusion, amount/ total dose), type of combination of drugs in each regimen, study design, type of cancer patients (chemonaïve/ previously untreated), neuropathy assessment tool, time of assessment of toxicity after treatment initiation and result presentation (acute versus chronic, time of occurrence of toxicity, degree of severity of symptoms, and measures taken).…”
Section: Discussionmentioning
confidence: 99%